Derailed: Communicating Singapore’s mass transit crises [Case study] - PANG, A. (Institutional Knowledge at Singapore Management University, 2013)
The case: In December 2011, one of Singapore’s main mass transit rail lines came to a standstill for several hours on two separate days. While occasional public transport breakdowns are unavoidable, the rail operator came under intense criticism for its poor handling of the incidents, including its failure in crisis communication. Its value: This case can be used to illustrate a number of perspectives and concepts from the literature on crisis and organisational communication. Of particular contemporary interest is what the case shows about how communication technologies, including social media, should and should not be used by organisations.